No Compasso de Espera em Angola: Reflexão Crítica sobre a Reconfiguração Institucional e o Horizonte 2027 - Almeida, E. C. (V Congresso Internacional de Angolanística, 2026)
This paper analyzes the process of institutional reconfiguration in Angola from the 2017 presidential transition to the 2027 electoral horizon. The country is currently experiencing a period of "limbo" or a "holding pattern," characterized by the tension between the continuity of a dominant-party regime (MPLA), in power since 1975, and growing social pressure for effective democratic change. Through a critical analysis of constitutional engineering, the judicialization of politics, and the emergence of new opposition fronts, this study argues that the 2027 Horizon represents the ultimate test of the resilience of Angolan institutions and their capacity to manage transition without violent disruptions.